RETRACTED: Sport orientation and stages of selection in multiyear training in academic rowing in the context of pro-environmental behavior - Bayer Elena; Arakelyan Samvel; Aivazova Elena (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001